An Innovative and Integrated Approach for Using Energy from the Flooded Coal Mines for Pre-warming of a Gas Engine in Standby Mode Using GSHP. (May 2017) - Athresh, Anup P.; Al-Habaibeh, Amin; Parker, Keith
Abstract: The effort to reduce energy consumption and carbon emission is driving companies to integrate multiple energy technologies to achieve the goal of reducing overall energy consumption, enhancing efficiency and decreasing operational cost. This paper outlines an innovative approach for integrating energy from flooded coal mines via a Ground Source Heat Pump (GSHP) to provide heating to buildings and at the same time to pre-warm a gas engine in standby mode. Once operational, the gas engine will produce significant waste heat that will replace the GSHP in heating the buildings. The results show that this energy integration technology provides much improved overall Coefficient of Performance and reduce carbon emission.